Genetic identification of Iberian rodent species using both mitochondrial and nuclear loci: application to noninvasive sampling. (24th October 2012) - Barbosa, S.; Pauperio, J.; Searle, J. B.; Alves, P. C.
Abstract Species identification through noninvasive sampling is increasingly used in animal conservation genetics, given that it obviates the need to handle free‐living individuals. Noninvasive sampling is particularly valuable for elusive and small species such as rodents. Although rodents are not usually assumed to be the most obvious target for conservation, of the 21 species or near‐species present in Iberia, three are considered endangered and declining, while several others are poorly studied. Here, we develop a genetic tool for identifying all rodent species in Iberia by noninvasive genetic sampling. To achieve this purpose, we selected one mitochondrial gene [cytochrome b (cyt‐b)] and one nuclear gene [interphotoreceptor retinoid‐binding protein (IRBP)], which we first sequenced using tissue samples. Both genes allow for the phylogenetic distinction of all species except the sibling species Microtus lusitanicus and Microtus duodecimcostatus. Overall, cyt‐b showed higher resolution than IRBP, revealing a clear barcoding gap. To allow these markers to be applied to noninvasive samples, we selected a short highly diagnostic fragment from each gene, which we used to obtain sequences from faeces and bones from owl pellets. Amplification success for the cyt‐b and IRBP fragment was 85% and 43% in faecal and 88% and 64% in owl‐pellet DNA extractions, respectively. The method allows the unambiguous identification of the great majority of Iberian rodent species from noninvasive samples, with application in studies of distribution, spatial ecology and population dynamics, and for conservation.